2007
DOI: 10.1002/j.2048-7940.2007.tb00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Reduce Risk of Fall-Related Injuries in Rehabilitation Nursing

Abstract: Rehabilitation nurses are in a critical position to lead interdisciplinary team fall prevention management, including injury risk reduction. This article provides an update for rehabilitation nurses on evidence-based strategies to reduce patients'risk of fall-related injuries. This content builds on existing literature by focusing on knowledge to promote patient responses that reduce the risk of falls and ultimately fall-related injuries. Although rehabilitation nurses understand the complex nature of falls, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…A geographical layout that kept patients within sight of the nurses’ station allowed nurses to know their patients as safe. Research has shown that ward layouts and designs that decrease patient visibility increase fall rates (Quigley et al. 2007).…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…A geographical layout that kept patients within sight of the nurses’ station allowed nurses to know their patients as safe. Research has shown that ward layouts and designs that decrease patient visibility increase fall rates (Quigley et al. 2007).…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…Taking these facts into consideration, it is obvious that all our efforts should go towards preventing first and second hip fractures. Different strategies to prevent hip fractures and consequent hip fracture surgery have been introduced to reduce the incidence of a second hip fracture [8–10]. An alternative approach to prevention could be femorplasty of the contra-lateral hip during the surgery of the first hip fracture [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Although safety checklists for home environments are commonly employed by rehabilitation and medical professionals, it is more important to examine how an individual uses and perceives his or her environment than to examine the actual components of that environment. Specifically, individuals with cognitive impairment may misinterpret the safety of a given environment or use poor judgment (Quigley, Bulat & Hart-Hughes, 2007).…”
Section: Environmentmentioning
confidence: 99%